Aplikasi Point of sale Berbasis Website pada Toko Sembako Tegar - Prayogi, Bayu Setyo; Fitri, Iskandar; Nuraini, Rini (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The development of the business world always requires us to improve the quality of products and services to consumers. goods purchasing services can be done electronically and can also be done online or in electronic commerce. Not a few entrepreneurs or business owners still manage their business transaction data manually, which of course has a high risk of losing data or making financial calculations wrong. Therefore, this website-based Point of sale application was designed with the aim of reducing these shortcomings and making it easier for entrepreneurs to manage their company's transaction data. This website-based Point of sale application has several advantages such as: facilitating transaction data management, simplifying business financial calculations, a computerized monthly financial recapitulation of the business.